Advances in the analysis and design of marine structures : proceedings of the 9th International Conference on Marine Structures (MARSTRUCT 2023, Gothenburg, Sweden, 3-5 April 2023) /: proceedings of the 9th International Conference on Marine Structures (MARSTRUCT 2023, Gothenburg, Sweden, 3-5 April 2023). (2023) - Unknown
No abstract available